DIFFERENTIAL DIAGNOSIS OF EPILEPTIC SEIZURES IN CRYPTOGENIC FOCAL FRONTAL LOBE EPILEPSY VERSUS PSYCHOGENIC NON-EPILEPTIC PAROXYSMS (A CASE REPORT) - N. V. Chebanenko; M. B. Mironov; S. G. Burd; O. I. Kudrayvtzeva; M. N. Sarzhina; M. M. Gunchenko; T. M. Krasilshikova; T. T. Batysheva (Эпилепсия и пароксизмальные состояния, 2017)
The report addresses the causes and diagnostic problems of cryptogenic focal frontal epilepsy. A clinical case of a patient with cryptogenic focal frontal epilepsy is presented. In this patient, epileptic seizures have long been considered as psychogenic non-epileptic paroxysms.